2004
DOI: 10.1016/j.amjhyper.2004.03.668
|View full text |Cite
|
Sign up to set email alerts
|

The impact of third-generation Beta-blocker antihypertensive treatment on endothelial function and the prothrombotic stateEffects of smoking

Abstract: In hypertensive smokers, nebivolol resulted in a significant decrease of plasma PAI-1, fibrinogen and homocystine. Celiprolol also significantly affected these parameters but to a lesser degree, whereas carvedilol had no significant favorable action. In nonsmokers, homocystine was reduced significantly by nebivolol. We conclude that smoking status should be a determinant of antihypertensive treatment choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 26 publications
1
14
0
5
Order By: Relevance
“…Similar to the results obtained with metoprolol, administration of up to 100 mg per day of atenolol over six months did not change levels of tPA-Ag and PAI-1-Ag or PAI-1 activity (26). In another study (1), 550 consecutive patients with uncomplicated hypertension were treated with celiprolol, carvedilol or nebivolol monotherapy. Plasma levels of fibrinogen and homocysteine, and serum levels of PAI-1 decreased in the celiprololand nebivolol-treated groups.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similar to the results obtained with metoprolol, administration of up to 100 mg per day of atenolol over six months did not change levels of tPA-Ag and PAI-1-Ag or PAI-1 activity (26). In another study (1), 550 consecutive patients with uncomplicated hypertension were treated with celiprolol, carvedilol or nebivolol monotherapy. Plasma levels of fibrinogen and homocysteine, and serum levels of PAI-1 decreased in the celiprololand nebivolol-treated groups.…”
Section: Discussionsupporting
confidence: 59%
“…It regulates thrombogenicity, vascular tone, leukocyte adhesion, and platelet and smooth muscle function (1). While normal endothelium is in a nonthrombotic state, deterioration of the vascular endothelium results in the synthesis and release of procoagulant and anticoagulant substances from the disrupted vascular endothelium (2,3).…”
mentioning
confidence: 99%
“…An existing study has shown that the effects of nebivolol on endothelial function and the prothrombotic state were more pronounced in hypertensive smokers than in hypertensive nonsmokers (as measured by decreases in fibrinogen, plasminogen activator inhibitor-I, and homocysteine [Vyssoulis et al 2004]). The failure of the beta-blockers, celiprolol and carvedilol, to elicit such pronounced effects in the same study demonstrates that the finding was unique to nebivolol and was not a class effect.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in animal models of coronary artery occlusion and reperfusion, localized endothelial swelling and protrusions, are predominantly confined to the capillary bed [12], indicating that endothelial dysfunction plays an important role in tissuelevel perfusion. Notably, carvedilol is an alpha1 and nonselective beta-adrenergic receptor antagonist with antioxidative properties known to protect against endothelial dysfunction [13][14][15]; we hypothesized that it may be also effective in preventing from myocardial no-reflow. Furthermore, myocardial no-reflow was always associated with microvascular structural disintegrity (structural no-reflow), which caused vascular leakiness.…”
Section: Introductionmentioning
confidence: 99%